Good scientific practice of using worldwide post-marketing surveillance data to ensure safety with HAALI BDDE cross-linked hyaluronic acid fillers - Hema Sundaram; Beatriz Molina; Editta Buttura da Prato; Gabriel Siquier-Dameto; Michela Zazzaron; Clara Cigni; Franco Grimolizzi (Drugs in Context)
Background: Aliaxin fillers (HAALI), produced by IBSA Farmaceutici Italia SrL (Italy), are biodegradable, non-pyrogenic, 1,4-butanediol diglycidyl ether cross-linked hyaluronic acid (HA) hydrogels. The formulations are tailored for different clinical indications, ensuring precise and natural outcomes. Their cohesivity and tissue integration capabilities are associated with relatively few adverse events (AEs), supporting their widespread use in aesthetic treatments. This article examines the real-world safety profile of HAALI fillers derived from worldwide post-marketing surveillance data.